A core-shell nanoprobe, a preparation method and application thereof
Patent Information
- Application Number
- CN202511636682.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-10
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-11-10
AI Technical Summary
[0004]针对现有MPI探针“常亮”所致肿瘤外背景高、对比度低、微病灶易漏检的瓶颈,本发明提供一种高成像信噪比的响应型核壳纳米探针、制备方法及其在磁粒子成像的应用
本发明提供一种核壳纳米探针,包括磁核和位于磁核外部的具有响应磁屏蔽功能的纳米外壳,所述纳米外壳在肿瘤微环境条件下结构崩塌;所述磁核的饱和磁化强度≥50emu/g,矫顽力≤5 Oe;所述纳米外壳饱的和磁化强度<50 emu/g,矫顽力>5 Oe。该核壳纳米探针通过独特的磁性核壳结构设计与肿瘤微环境响应特性,能够实现高信噪比的肿瘤成像功能。其中,磁核采用高信号的磁性纳米颗粒为内核,以低信号且具有响应磁屏蔽功能的纳米颗粒为外壳,高信号的磁性纳米颗粒为内核能够提供强磁信号基础,确保探针在体外磁场中的高响应性。处于非肿瘤微环境时,低信号且具有响应磁屏蔽功能的纳米外壳能够有效形成磁屏蔽层,抑制背景信号干扰。当处于肿瘤微环境时,外壳的结构“崩塌”,使磁核被“裸露”出来,实现“关闭-开启”式磁信号切换,从而产生较高的磁粒子传感信号响应实现磁信号的可控释放,以提升成像对比度,突破传统MPI探针“全程亮”的瓶颈,实现肿瘤特异性的“点亮即定位”,从而能够更灵敏地确定病灶部位,便于微小病灶检出。其“静默-激活”式信号调控机制不仅提升了肿瘤检测的精准度,还为诊疗一体化提供了新型工具,具有显著的临床转化潜力。
Smart Images

Figure CN121287954B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of magnetic particle imaging technology, specifically to a core-shell nanoprobe, its preparation method, and its application, particularly a high-signal-to-noise ratio responsive core-shell nanoprobe, its preparation method, and its application in magnetic particle imaging. Background Technology
[0002] Magnetic Particle Imaging (MPI), as an emerging medical imaging technology, has rapidly become a research hotspot in the field of biomedical imaging since its inception, thanks to its unique physical mechanisms and significant technological advantages. Compared with traditional medical imaging techniques such as Magnetic Resonance Imaging (MRI), Computed Tomography (CT), and Positron Emission Tomography (PET), MPI possesses many irreplaceable characteristics. The core principle of MPI is based on the detection of the nonlinear magnetization response of magnetic nanoparticles under an alternating magnetic field. This detection method enables MPI to achieve truly quantitative imaging, meaning that the signal intensity of each pixel in the image has a strictly linear relationship with the concentration of magnetic particles in the corresponding region, providing a reliable quantitative basis for accurate disease diagnosis and treatment monitoring. With the continuous deepening of biomedical research, higher demands are being placed on the early diagnosis and precise treatment of diseases. MPI technology, with its advantages of quantification, real-time processing, high sensitivity, and lack of tissue penetration depth limitations, not only provides a powerful tool for biomedical research but also brings new hope for improving the accuracy of disease diagnosis and treatment outcomes.
[0003] However, current MPI probes generally face the problem of background signal interference caused by non-specific uptake by organs of the Mononuclear Phagocyte System (RES), such as the liver and spleen. Due to the large amount of probe uptake by RES organs, the signal intensity of organs like the liver and spleen is much higher than that of the lesion area during imaging, resulting in reduced contrast between the lesion and surrounding tissue in the image. This low-contrast image not only affects the doctor's accurate judgment of the lesion but may also lead to missed diagnoses of small lesions, severely limiting the lesion detection capability of MPI. Secondly, the magnetic properties of existing MPI probes are mostly statically designed, lacking responsiveness to the tumor microenvironment. During imaging, the signal difference of the probe in the lesion and normal tissue mainly depends on the concentration gradient; that is, a strong signal is only generated when the probe concentration in the lesion area is higher than that in normal tissue. However, this concentration gradient is often affected by various factors, such as blood circulation and tissue penetration, leading to unstable signal differences, further limiting the improvement of imaging sensitivity and making it difficult to meet the diagnostic needs of complex diseases. The tumor microenvironment has unique physical and chemical properties, such as a low pH value and high concentrations of reducing substances (such as glutathione). These characteristics provide an opportunity to design intelligent responsive probes. Existing responsive MPI probes use "ON-OFF" imaging, followed by lesion identification through reverse enhancement-subtraction strategies. However, this method not only increases the complexity and time cost of imaging but also often operates in a "constantly lit" state, resulting in high background and low contrast outside the tumor, making it easy to miss microlesions and failing to fundamentally solve the problem of background signal interference. Therefore, developing an MPI probe that can respond to the tumor microenvironment, dynamically adjust magnetic properties, and significantly reduce RES background signal is of great significance for improving the signal-to-noise ratio and sensitivity of MPI imaging. Summary of the Invention
[0004] To address the bottlenecks of existing MPI probes, such as high background noise, low contrast, and easy missed detection of microlesions due to their constant illumination, this invention provides a high signal-to-noise ratio responsive core-shell nanoprobe, its preparation method, and its application in magnetic particle imaging. To achieve the above objectives, this invention employs the following technical solutions: This invention provides a core-shell nanoprobe, comprising a magnetic core and a nanoshell with responsive magnetic shielding function located outside the magnetic core. The nanoshell collapses under tumor microenvironment conditions. The saturation magnetization of the magnetic core is ≥50 emu / g, and the coercivity is ≤5 Oe. The saturation magnetization of the nanoshell is <50 emu / g, and the coercivity is >5 Oe.
[0005] Optionally, the magnetic core is an oil-phase magnetic core Fe3O4 nanoparticle.
[0006] Optionally, the nanoshell is a nanoshell doped with transition metal elements.
[0007] Optionally, the transition metal element includes one or more of Mn, Co, and Ni.
[0008] The preparation methods for the core-shell nanoprobes described above include: The magnetic nucleus particles, the first iron source, the transition metal source, phenylbenzoic acid, and oleic acid are dissolved in dibenzyl ether to form a first mixture. The first mixture was degassed and then subjected to pyrolysis to obtain a core-shell nanoprobe.
[0009] Optionally, the molar ratio of the magnetic nucleus particles, the first iron source, the transition metal source, phenylbenzoic acid, oleic acid and dibenzyl ether is (0.11-0.19):(0.11-0.71):(0.11-0.71):(2-3.65):(3.2-9.5):(42-79).
[0010] Optionally, the temperature for pyrolysis of the first mixture is 280-320 °C, the reaction time is 0.5-1 h, and the heating rate is 3-8 °C / min; the first iron source is one or more of ferric acetylacetone, ferric oleate, ferrous acetylacetone, ferrous acetate, and ferrous gluconate; the transition metal source is one or more of manganese acetylacetone, manganese carbonate, manganese acetate, manganese chloride, cobalt acetylacetone, cobalt chloride, cobalt nitrate, cobalt acetate, nickel acetylacetone, nickel chloride, nickel nitrate, and nickel acetate.
[0011] Optionally, the magnetic core particles are oil-phase magnetic core Fe3O4 nanoparticles, and the preparation method of the oil-phase magnetic core Fe3O4 nanoparticles is as follows: The second iron source, phenylbenzoic acid, and oleic acid are dissolved in dibenzyl ether solvent to form a second mixture; The second mixture was degassed and then subjected to pyrolysis to obtain oil-phase magnetic core Fe3O4 nanoparticles.
[0012] Optionally, the second iron source is one or more of ferric acetylacetone, ferric oleate, ferrous acetylacetone, ferrous acetate, and ferrous gluconate; in the second mixture, the molar ratio of the second iron source, phenylbenzoic acid, oleic acid, and dibenzyl ether is (1.9-2.8):(2-3.65):(3.2-9.5):(42-79); the temperature for pyrolysis of the second mixture is 280-320 °C, the heating rate is 15-25 °C / min, and the reaction time is 0.5-1 h.
[0013] The above-mentioned core-shell nanoprobes are used in magnetic particle imaging.
[0014] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a core-shell nanoprobe comprising a magnetic core and a responsive magnetic shielding nanoshell located outside the magnetic core. The nanoshell collapses under tumor microenvironment conditions. The magnetic core has a saturation magnetization ≥50 emu / g and a coercivity ≤5 Oe; the nanoshell has a saturation magnetization <50 emu / g and a coercivity >5 Oe. This core-shell nanoprobe, through its unique magnetic core-shell structure design and tumor microenvironment response characteristics, can achieve high signal-to-noise ratio tumor imaging. The magnetic core uses high-signal magnetic nanoparticles as the core and low-signal nanoparticles with responsive magnetic shielding as the shell. The high-signal magnetic nanoparticle core provides a strong magnetic signal basis, ensuring high responsiveness of the probe in an external magnetic field. In a non-tumor microenvironment, the low-signal nanoshell with responsive magnetic shielding effectively forms a magnetic shielding layer, suppressing background signal interference. When in the tumor microenvironment, the outer shell structure "collapses," exposing the magnetic nucleus and enabling a "shutdown-on" magnetic signal switching. This generates a high magnetic particle sensing signal response, allowing for the controlled release of magnetic signals to improve imaging contrast. This overcomes the bottleneck of traditional MPI probes being "always on," achieving tumor-specific "light-up-and-locate" detection. This allows for more sensitive identification of lesion sites, facilitating the detection of even small lesions. Its "silent-activated" signal modulation mechanism not only improves the accuracy of tumor detection but also provides a novel tool for integrated diagnosis and treatment, demonstrating significant clinical translational potential.
[0015] This invention also provides a method for preparing the core-shell nanoprobe as described above. This method involves dissolving magnetic core particles, a first iron source, a transition metal source, phenylbenzoic acid, and oleic acid in a dibenzyl ether solvent to form a first mixture. The first mixture is then degassed and subjected to pyrolysis to obtain the core-shell nanoprobe. After removing oxygen through degasing, high-temperature pyrolysis triggers the simultaneous thermal decomposition of the first iron source and the transition metal source, resulting in the in-situ growth of a highly coercive outer shell on the surface of the magnetic core Fe3O4 nanoparticles. Simultaneously, phenylbenzoic acid and oleic acid synergistically regulate the lattice structure of the outer shell, forming a magnetic shielding layer. Transition metal doping can endow the outer shell with different magnetic shielding capabilities. The structure of the outer shell can react under tumor microenvironment conditions, leading to its collapse. This method constructs the shell structure through a single pyrolysis. By adjusting the ratio of iron source to transition metal, the saturation magnetization and coercivity of the shell can be precisely controlled, achieving complementary magnetic properties between the shell and the magnetic core. The method is simple, the reaction conditions are mild, and there is no need for complex equipment or harsh reaction conditions. Moreover, the prepared core-shell nanoprobes can effectively resist the background signal interference caused by non-specific uptake by mononuclear phagocytic organs such as the liver and spleen under normal conditions. Under acidic conditions, the shell structure can collapse, enhancing the imaging contrast of the probe, thereby enabling more sensitive identification of lesion sites. It has excellent practicality and economy.
[0016] As mentioned above, the application of core-shell nanoprobes in magnetic particle imaging (MPI) can significantly improve the detection sensitivity and clinical applicability of MPI, promote the clinical translation of MPI, and facilitate its application in tumor imaging (including but not limited to breast cancer, lung cancer, colorectal cancer, etc.), gastric ulcers, gout, and other fields. It provides technical support for early tumor diagnosis, intraoperative navigation, and efficacy evaluation. Attached Figure Description
[0017] Figure 1 This is a flowchart of the preparation method of the core-shell nanoprobe of the present invention.
[0018] Figure 2 This is a transmission electron microscope characterization image of the magnetic core Fe3O4 nanoparticles prepared in Comparative Example 1 of the present invention.
[0019] Figure 3 The image shows the transmission electron microscope characterization of the CoFe2O4 nanoparticles with nanoshells prepared in Comparative Example 2 of this invention.
[0020] Figure 4 Transmission electron microscopy characterization of the core-shell nanoprobe (SHNP) prepared in Example 1 of the present invention.
[0021] Figure 5 The image shows the dynamic light scattering particle size distribution of the magnetic core Fe3O4 prepared in Comparative Example 1, the nanoshell CoFe2O4 prepared in Comparative Example 2, and the core-shell nanoprobe (SHNP) prepared in Example 1 of this invention.
[0022] Figure 6 Magnetization curves of the magnetic core Fe3O4 prepared in Comparative Example 1, the nanoshell CoFe2O4 prepared in Comparative Example 2, and the core-shell nanoprobe (SHNP) prepared in Example 1 are shown.
[0023] Figure 7 The MPS signal intensity diagrams are of the magnetic core Fe3O4 prepared in Comparative Example 1, the nanoshell CoFe2O4 prepared in Comparative Example 2, and the core-shell nanoprobe (SHNP) prepared in Example 1.
[0024] Figure 8 The MPI signal intensity diagrams are of the magnetic core Fe3O4 prepared in Comparative Example 1, the nanoshell CoFe2O4 prepared in Comparative Example 2, and the core-shell nanoprobe (SHNP) prepared in Example 1.
[0025] Figure 9 The MPI relative signal intensity diagram of the core-shell nanoprobe (SHNP) prepared in Example 1 of the present invention after 12 h of buffer response at different pH values.
[0026] Figure 10The MPI relative signal intensity diagram of the core-shell nanoprobe (SHNP) prepared in Example 1 of the present invention after responding to different times in a buffer solution at pH 5.4.
[0027] Figure 11 Transmission electron microscopy characterization of the core-shell nanoprobe (SHNP) prepared in Example 1 of the present invention after 2 hours of response in a buffer solution at pH 5.4.
[0028] Figure 12 Image signal intensity of subcutaneous breast cancer tumors using the core-shell nanoprobe (SHNP) prepared in Example 1 of this invention. Detailed Implementation
[0029] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.
[0030] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.
[0031] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values (including integers and fractions) within those ranges.
[0032] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”
[0033] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.
[0034] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0035] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.
[0036] The present invention will be further described in detail below with reference to specific embodiments. These descriptions are for explanation purposes only and are not intended to limit the scope of the invention.
[0037] This invention provides a core-shell nanoprobe, comprising a magnetic core and a nanoshell with responsive magnetic shielding function located outside the magnetic core. The nanoshell collapses under tumor microenvironment conditions. The magnetic core has a saturation magnetization ≥ 50 emu / g and a coercivity ≤ 5 Oe; the nanoshell has a saturation magnetization < 50 emu / g and a coercivity > 5 Oe. Preferably, the magnetic core is an oil-phase Fe3O4 nanoparticle; the nanoshell is a nanoshell doped with a transition metal element. More preferably, the transition metal element includes one or more of Mn, Co, and Ni.
[0038] This core-shell nanoprobe achieves high signal-to-noise ratio tumor imaging through its unique magnetic core-shell structure and tumor microenvironment responsiveness. The magnetic core utilizes high-signal magnetic nanoparticles as the inner core and low-signal nanoparticles with responsive magnetic shielding as the outer shell. The high-signal magnetic nanoparticles provide a strong magnetic signal foundation, ensuring high responsiveness of the probe in an external magnetic field. In a non-tumor microenvironment, the low-signal nanoshell with responsive magnetic shielding effectively forms a magnetic shielding layer, suppressing background signal interference. When in a tumor microenvironment, the outer shell structure "collapses," exposing the magnetic core and enabling "off-on" magnetic signal switching. This significantly improves the imaging signal-to-noise ratio, overcoming the bottleneck of traditional MPI probes that are "always lit," characterized by high background noise, poor contrast, and difficulty in detecting small lesions outside the tumor. This achieves tumor-specific "light-up-and-localize" imaging.
[0039] See Figure 1 The present invention also provides a method for preparing the core-shell nanoprobe as described above, comprising: S1: The magnetic nucleus particles, the first iron source, the transition metal source, phenylbenzoic acid, and oleic acid are dissolved in dibenzyl ether solvent to form the first mixture, specifically: A first mixture is obtained by mixing magnetic nuclei, a first iron source, a transition metal source, phenylbenzoic acid, oleic acid, and dibenzyl ether solvent in a molar ratio of (0.11-0.19):(0.11-0.71):(0.11-0.71):(2-3.65):(3.2-9.5):(42-79). Preferably, the first iron source is one or more of ferric acetylacetone, ferric oleate, ferrous acetylacetone, ferrous acetate, and ferrous gluconate; the transition metal source is one or more of manganese acetylacetone, manganese carbonate, manganese acetate, manganese chloride, cobalt acetylacetone, cobalt chloride, cobalt nitrate, cobalt acetate, nickel acetylacetone, nickel chloride, nickel nitrate, and nickel acetate.
[0040] Preferably, the magnetic core particles are oil-phase magnetic core Fe3O4 nanoparticles, and the preparation method of the oil-phase magnetic core Fe3O4 nanoparticles is as follows: The second iron source, phenylbenzoic acid, oleic acid, and dibenzyl ether are mixed in a molar ratio of (1.9-2.8):(2-3.65):(3.2-9.5):(42-79) to form a second mixture. The second mixture was first degassed at room temperature for 1-3 h under magnetic stirring to remove oxygen. Then, under nitrogen protection, it was pyrolyzed at 280-320 ℃ for 0.5-1 h at a temperature of 15-25 ℃ / min. After washing with n-hexane and anhydrous ethanol, oil-phase magnetic core Fe3O4 nanoparticles were obtained.
[0041] The second iron source is one or more of ferric acetylacetone, ferric oleate, ferrous acetylacetone, ferrous acetate, and ferrous gluconate.
[0042] S2: The first mixture is degassed and then subjected to pyrolysis to obtain a core-shell nanoprobe, specifically: The first mixture was degassed at room temperature for 1-3 h under magnetic stirring to remove oxygen. Then, under nitrogen protection, it was pyrolyzed at 280-320 °C for 0.5-1 h at a rate of 3-8 °C / min. After washing with n-hexane and anhydrous ethanol, the core-shell nanoprobe was obtained.
[0043] This method involves degassing to remove oxygen, followed by high-temperature pyrolysis to trigger the co-precipitation of a first iron source and a transition metal source. This results in the in-situ growth of a highly coercive shell on the surface of the magnetic nucleus particles. Simultaneously, phenylbenzoic acid and oleic acid synergistically regulate the shell's lattice structure, forming a magnetic shielding layer. Transition metal doping imparts sensitive properties to the shell, and the carboxylic acid groups in the shell react under tumor microenvironment conditions, leading to the collapse of the shell structure. This method completes the shell structure construction through a single pyrolysis. By adjusting the ratio of iron source to transition metal, the saturation magnetization and coercivity of the shell can be precisely controlled, achieving complementary magnetic properties between the shell and the magnetic nucleus. The method is simple, with mild reaction conditions, requiring no complex equipment or harsh reaction conditions. Furthermore, the prepared core-shell nanoprobes can effectively resist background signal interference caused by non-specific uptake by mononuclear phagocytic organs such as the liver and spleen under normal conditions. Under acidic conditions, the shell structure collapses, enhancing the probe's imaging contrast and enabling more sensitive lesion location. This method demonstrates excellent practicality and cost-effectiveness.
[0044] Example 1 2 mmol of ferric acetylacetone, 2.02 mmol of 4-phenylbenzoic acid, 4.50 mmol of oleic acid, and 52.6 mmol of dibenzyl ether were stirred in a 50 mL three-necked flask to obtain a second mixture. The second mixture was placed in a temperature-controlled apparatus and, under magnetic stirring, degassed at room temperature for 1 h to remove oxygen. Subsequently, N2 protective gas was introduced into the second mixture, and the temperature was increased to 290 °C at a rate of 20 °C / min and maintained for 0.5 h. After the reaction was complete, the mixture was cooled to room temperature. Oil-phase magnetic core Fe3O4 nanoparticles were obtained by washing with n-hexane and anhydrous ethanol.
[0045] 0.15 mmol of oil-phase magnetic core Fe3O4 nanoparticles, 0.566 mmol of iron acetylacetone, 0.5 mmol of cobalt acetylacetone, 2.02 mmol of 4-phenylbenzoic acid, 3.80 mmol of oleic acid, and 56.0 mmol of dibenzyl ether were placed in a 50 mL round-bottom flask and mixed thoroughly to obtain a first mixture. This first mixture was placed in a temperature-controlled device and degassed for 1 h under magnetic stirring. The temperature was then increased to 290 °C at a rate of 3.3 °C / min and maintained at this temperature for 0.5 h to carry out a thermal decomposition reaction. After the reaction was completed, the mixture was cooled to room temperature. The oil-phase core-shell nanoprobe (denoted as SHNP) was obtained by washing with n-hexane and anhydrous ethanol.
[0046] Example 2 1.9 mmol ferric oleate, 2 mmol 4-phenylbenzoic acid, 3.2 mmol oleic acid, and 42 mmol dibenzyl ether were stirred in a 50 mL three-necked flask to obtain a second mixture. The second mixture was placed in a temperature-controlled apparatus and, under magnetic stirring, degassed at room temperature for 2 h to remove oxygen. Subsequently, N2 protective gas was introduced into the second mixture, and the temperature was increased to 280 °C at a rate of 15 °C / min and maintained for 1 h. After the reaction was complete, the mixture was cooled to room temperature. Oil-phase magnetic core Fe3O4 nanoparticles were obtained by washing with n-hexane and anhydrous ethanol.
[0047] 0.11 mmol of oil-phase magnetic core Fe3O4 nanoparticles, 0.11 mmol of ferric oleate, 0.11 mmol of manganese carbonate, 2 mmol of 2-phenylbenzoic acid, 3.2 mmol of oleic acid, and 42.0 mmol of dibenzyl ether were placed in a 50 mL round-bottom flask and mixed thoroughly to obtain a first mixture. This first mixture was placed in a temperature-controlled device and degassed for 1 h under magnetic stirring. The temperature was then increased to 280 °C at a rate of 3 °C / min and maintained at this temperature for 1 h to carry out a thermal decomposition reaction. After the reaction was completed, the mixture was cooled to room temperature. The nanoparticles were washed with n-hexane and anhydrous ethanol to obtain the oil-phase core-shell nanoprobe.
[0048] Example 3 2.8 mmol ferrous acetate, 3.65 mmol 4-phenylbenzoic acid, 9.5 mmol oleic acid, and 79 mmol dibenzyl ether were placed in a 50 mL three-necked flask and stirred to obtain a second mixture. The second mixture was placed in a temperature-controlled apparatus and, under magnetic stirring, degassed at room temperature for 2 h to remove oxygen. Subsequently, N2 protective gas was introduced into the second mixture, and the temperature was increased to 320 °C at a rate of 25 °C / min and maintained for 0.5 h. After the reaction was complete, the mixture was cooled to room temperature. Oil-phase magnetic core Fe3O4 nanoparticles were obtained by washing with n-hexane and anhydrous ethanol.
[0049] 0.19 mmol of oil-phase magnetic core Fe3O4 nanoparticles, 0.71 mmol of ferrous gluconate, 0.71 mmol of cobalt nitrate, 3.65 mmol of 2-phenylbenzoic acid, 9.5 mmol of oleic acid, and 79 mmol of dibenzyl ether were placed in a 50 mL round-bottom flask and mixed thoroughly to obtain a first mixture. This first mixture was placed in a temperature-controlled device and degassed for 1 h under magnetic stirring. The temperature was then increased to 320 °C at a rate of 8 °C / min and maintained at this temperature for 1 h to carry out a thermal decomposition reaction. After the reaction was completed, the mixture was cooled to room temperature. The nanoparticles were washed with n-hexane and anhydrous ethanol to obtain the oil-phase core-shell nanoprobe.
[0050] Example 4 2.5 mmol ferrous gluconate, 3.2 mmol 4-phenylbenzoic acid, 7 mmol oleic acid, and 60 mmol dibenzyl ether were stirred in a 50 mL three-necked flask to obtain a second mixture. The second mixture was placed in a temperature-controlled apparatus and, under magnetic stirring, degassed at room temperature for 2 h to remove oxygen. Subsequently, N2 protective gas was introduced into the second mixture, and the temperature was increased to 300 °C at a rate of 23 °C / min and maintained for 0.8 h. After the reaction was complete, the mixture was cooled to room temperature. Oil-phase magnetic core Fe3O4 nanoparticles were obtained by washing with n-hexane and anhydrous ethanol.
[0051] 0.16 mmol of oil-phase magnetic core Fe3O4 nanoparticles, 0.4 mmol of ferrous acetate, 0.3 mmol of nickel acetate, 3 mmol of 2-phenylbenzoic acid, 6 mmol of oleic acid, and 70 mmol of dibenzyl ether were placed in a 50 mL round-bottom flask and mixed thoroughly to obtain a first mixture. The first mixture was placed in a temperature-controlled device and degassed for 1 h under magnetic stirring. Then, the temperature was increased to 300 °C at a rate of 6 °C / min and maintained at this temperature for 0.8 h to carry out a thermal decomposition reaction. After the reaction was completed, the mixture was cooled to room temperature. The nanoparticles were washed with n-hexane and anhydrous ethanol to obtain the oil-phase core-shell nanoprobe.
[0052] Example 5 A mixture of 2 mmol ferrous acetylacetone and ferric acetylacetone, 2.5 mmol 4-phenylbenzoic acid, 4 mmol oleic acid, and 52 mmol dibenzyl ether was stirred in a 50 mL three-necked flask to obtain a second mixture. The second mixture was placed in a temperature-controlled apparatus and, under magnetic stirring, degassed at room temperature for 2 h to remove oxygen. Subsequently, N2 protective gas was introduced into the second mixture, and the temperature was increased to 310 °C at a rate of 22 °C / min and maintained for 0.8 h. After the reaction was complete, the mixture was cooled to room temperature. Oil-phase magnetic core Fe3O4 nanoparticles were obtained by washing with n-hexane and anhydrous ethanol.
[0053] 0.17 mmol of oil-phase magnetic core Fe3O4 nanoparticles, a mixture of 0.2 mmol of ferric oleate and ferrous acetylacetone, 0.2 mmol of nickel acetylacetone, 8 mmol of 2-phenylbenzoic acid, 7 mmol of oleic acid, and 65 mmol of dibenzyl ether were placed in a 50 mL round-bottom flask and mixed thoroughly to obtain a first mixture. The first mixture was placed in a temperature-controlled device and degassed for 1 h under magnetic stirring. Then, the temperature was increased to 310 °C at a rate of 7 °C / min and maintained at this temperature for 0.8 h to carry out a thermal decomposition reaction. After the reaction was completed, the mixture was cooled to room temperature. The nanoparticles were washed with n-hexane and anhydrous ethanol to obtain the oil-phase core-shell nanoprobe.
[0054] Example 6 2 mmol of ferric acetylacetone, 2.02 mmol of 4-phenylbenzoic acid, 4.50 mmol of oleic acid, and 52.6 mmol of dibenzyl ether were stirred in a 50 mL three-necked flask to obtain a second mixture. The second mixture was placed in a temperature-controlled apparatus and, under magnetic stirring, degassed at room temperature for 1 h to remove oxygen. Subsequently, N2 protective gas was introduced into the second mixture, and the temperature was increased to 290 °C at a rate of 20 °C / min and maintained for 0.5 h. After the reaction was complete, the mixture was cooled to room temperature. Oil-phase magnetic core Fe3O4 nanoparticles were obtained by washing with n-hexane and anhydrous ethanol.
[0055] 0.15 mmol of oil-phase magnetic core Fe3O4 nanoparticles, 0.566 mmol of iron acetylacetone, 0.5 mmol of nickel acetylacetone, 2.02 mmol of 2-phenylbenzoic acid, 3.80 mmol of oleic acid, and 56.0 mmol of dibenzyl ether were placed in a 50 mL round-bottom flask and mixed thoroughly to obtain a first mixture. The first mixture was placed in a temperature-controlled device and degassed for 1 h under magnetic stirring. Then, the temperature was increased to 290 °C at a rate of 3.3 °C / min and maintained at this temperature for 0.5 h to carry out a thermal decomposition reaction. After the reaction was completed, the mixture was cooled to room temperature. The nanoparticles were washed with n-hexane and anhydrous ethanol to obtain the oil-phase core-shell nanoprobe.
[0056] Example 7 2 mmol of ferric acetylacetone, 2.02 mmol of 4-phenylbenzoic acid, 4.50 mmol of oleic acid, and 52.6 mmol of dibenzyl ether were stirred in a 50 mL three-necked flask to obtain a second mixture. The second mixture was placed in a temperature-controlled apparatus and, under magnetic stirring, degassed at room temperature for 1 h to remove oxygen. Subsequently, N2 protective gas was introduced into the second mixture, and the temperature was increased to 290 °C at a rate of 20 °C / min and maintained for 0.5 h. After the reaction was complete, the mixture was cooled to room temperature. Oil-phase magnetic core Fe3O4 nanoparticles were obtained by washing with n-hexane and anhydrous ethanol.
[0057] 0.15 mmol of oil-phase magnetic core Fe3O4 nanoparticles, 0.566 mmol of iron acetylacetone, 0.5 mmol of cobalt acetylacetone, 2.02 mmol of 2-phenylbenzoic acid, 3.80 mmol of oleic acid, and 56.0 mmol of dibenzyl ether were placed in a 50 mL round-bottom flask and mixed thoroughly to obtain a first mixture. The first mixture was placed in a temperature-controlled device and degassed for 1 h under magnetic stirring. Then, the temperature was increased to 290 °C at a rate of 3.3 °C / min and maintained at this temperature for 0.5 h to carry out a thermal decomposition reaction. After the reaction was completed, the mixture was cooled to room temperature. The nanoparticles were washed with n-hexane and anhydrous ethanol to obtain the oil-phase core-shell nanoprobe.
[0058] Example 8 2 mmol of ferric acetylacetone, 2.02 mmol of 4-phenylbenzoic acid, 4.50 mmol of oleic acid, and 52.6 mmol of dibenzyl ether were stirred in a 50 mL three-necked flask to obtain a second mixture. The second mixture was placed in a temperature-controlled apparatus and, under magnetic stirring, degassed at room temperature for 1 h to remove oxygen. Subsequently, N2 protective gas was introduced into the second mixture, and the temperature was increased to 290 °C at a rate of 20 °C / min and maintained for 0.5 h. After the reaction was complete, the mixture was cooled to room temperature. Oil-phase magnetic core Fe3O4 nanoparticles were obtained by washing with n-hexane and anhydrous ethanol.
[0059] 0.15 mmol of oil-phase magnetic core Fe3O4 nanoparticles, 0.566 mmol of iron acetylacetone, 0.5 mmol of manganese acetylacetone, 2.02 mmol of 2-phenylbenzoic acid, 3.80 mmol of oleic acid, and 56.0 mmol of dibenzyl ether were placed in a 50 mL round-bottom flask and mixed thoroughly to obtain a first mixture. This first mixture was placed in a temperature-controlled device and degassed for 1 h under magnetic stirring. The temperature was then increased to 290 °C at a rate of 3.3 °C / min and maintained at this temperature for 0.5 h to carry out a thermal decomposition reaction. After the reaction was completed, the mixture was cooled to room temperature. The nanoparticles were washed with n-hexane and anhydrous ethanol to obtain the oil-phase core-shell nanoprobe.
[0060] Example 9 2 mmol of ferric acetylacetone, 2.02 mmol of 4-phenylbenzoic acid, 4.50 mmol of oleic acid, and 52.6 mmol of dibenzyl ether were stirred in a 50 mL three-necked flask to obtain a second mixture. The second mixture was placed in a temperature-controlled apparatus and, under magnetic stirring, degassed at room temperature for 1 h to remove oxygen. Subsequently, N2 protective gas was introduced into the second mixture, and the temperature was increased to 290 °C at a rate of 20 °C / min and maintained for 0.5 h. After the reaction was complete, the mixture was cooled to room temperature. Oil-phase magnetic core Fe3O4 nanoparticles were obtained by washing with n-hexane and anhydrous ethanol.
[0061] 0.15 mmol of oil-phase magnetic core Fe3O4 nanoparticles, 0.566 mmol of iron acetylacetone, a mixture of nickel chloride and nickel nitrate (total molar amount 0.5 mmol), 2.02 mmol of 2-phenylbenzoic acid, 3.80 mmol of oleic acid, and 56.0 mmol of dibenzyl ether were placed in a 50 mL round-bottom flask and mixed thoroughly to obtain a first mixture. The first mixture was placed in a temperature-controlled device and degassed for 1 h under magnetic stirring. Then, the temperature was increased to 290 °C at a rate of 3.3 °C / min and maintained at this temperature for 0.5 h to carry out a thermal decomposition reaction. After the reaction was completed, the mixture was cooled to room temperature. The nanoparticles were washed with n-hexane and anhydrous ethanol to obtain the oil-phase core-shell nanoprobe.
[0062] Example 10 2 mmol of ferric acetylacetone, 2.02 mmol of 4-phenylbenzoic acid, 4.50 mmol of oleic acid, and 52.6 mmol of dibenzyl ether were stirred in a 50 mL three-necked flask to obtain a second mixture. The second mixture was placed in a temperature-controlled apparatus and, under magnetic stirring, degassed at room temperature for 1 h to remove oxygen. Subsequently, N2 protective gas was introduced into the second mixture, and the temperature was increased to 290 °C at a rate of 20 °C / min and maintained for 0.5 h. After the reaction was complete, the mixture was cooled to room temperature. Oil-phase magnetic core Fe3O4 nanoparticles were obtained by washing with n-hexane and anhydrous ethanol.
[0063] 0.15 mmol of oil-phase magnetic core Fe3O4 nanoparticles, 0.566 mmol of ferric acetylacetone, 0.5 mmol of a mixture of manganese acetate and manganese chloride (total molar amount), 2.02 mmol of 2-phenylbenzoic acid, 3.80 mmol of oleic acid, and 56.0 mmol of dibenzyl ether were placed in a 50 mL round-bottom flask and mixed thoroughly to obtain a first mixture. The first mixture was placed in a temperature-controlled device and degassed for 1 h under magnetic stirring. Then, the temperature was increased to 290 °C at a rate of 3.3 °C / min and maintained at this temperature for 0.5 h to carry out a thermal decomposition reaction. After the reaction was completed, the mixture was cooled to room temperature. The nanoparticles were washed with n-hexane and anhydrous ethanol to obtain the oil-phase core-shell nanoprobe.
[0064] Example 11 2 mmol of ferric acetylacetone, 2.02 mmol of 4-phenylbenzoic acid, 4.50 mmol of oleic acid, and 52.6 mmol of dibenzyl ether were stirred in a 50 mL three-necked flask to obtain a second mixture. The second mixture was placed in a temperature-controlled apparatus and, under magnetic stirring, degassed at room temperature for 1 h to remove oxygen. Subsequently, N2 protective gas was introduced into the second mixture, and the temperature was increased to 290 °C at a rate of 20 °C / min and maintained for 0.5 h. After the reaction was complete, the mixture was cooled to room temperature. Oil-phase magnetic core Fe3O4 nanoparticles were obtained by washing with n-hexane and anhydrous ethanol.
[0065] 0.15 mmol of oil-phase magnetic core Fe3O4 nanoparticles, 0.566 mmol of iron acetylacetone, 0.5 mmol of nickel acetate, 2.02 mmol of 2-phenylbenzoic acid, 3.80 mmol of oleic acid, and 56.0 mmol of dibenzyl ether were placed in a 50 mL round-bottom flask and mixed thoroughly to obtain a first mixture. The first mixture was placed in a temperature-controlled device and degassed for 1 h under magnetic stirring. Then, the temperature was increased to 290 °C at a rate of 3.3 °C / min and maintained at this temperature for 0.5 h to carry out a thermal decomposition reaction. After the reaction was completed, the mixture was cooled to room temperature. The nanoparticles were washed with n-hexane and anhydrous ethanol to obtain the oil-phase core-shell nanoprobe.
[0066] Example 12 2 mmol of ferric acetylacetone, 2.02 mmol of 4-phenylbenzoic acid, 4.50 mmol of oleic acid, and 52.6 mmol of dibenzyl ether were stirred in a 50 mL three-necked flask to obtain a second mixture. The second mixture was placed in a temperature-controlled apparatus and, under magnetic stirring, degassed at room temperature for 1 h to remove oxygen. Subsequently, N2 protective gas was introduced into the second mixture, and the temperature was increased to 290 °C at a rate of 20 °C / min and maintained for 0.5 h. After the reaction was complete, the mixture was cooled to room temperature. Oil-phase magnetic core Fe3O4 nanoparticles were obtained by washing with n-hexane and anhydrous ethanol.
[0067] 0.15 mmol of oil-phase magnetic core Fe3O4 nanoparticles, 0.566 mmol of iron acetylacetone, a mixture of 0.5 mmol of cobalt chloride and cobalt acetate, 2.02 mmol of 2-phenylbenzoic acid, 3.80 mmol of oleic acid, and 56.0 mmol of dibenzyl ether were placed in a 50 mL round-bottom flask and mixed thoroughly to obtain a first mixture. The first mixture was placed in a temperature-controlled device and degassed for 1 h under magnetic stirring. Then, the temperature was increased to 290 °C at a rate of 3.3 °C / min and maintained at this temperature for 0.5 h to carry out a thermal decomposition reaction. After the reaction was completed, the mixture was cooled to room temperature. The nanoparticles were washed with n-hexane and anhydrous ethanol to obtain the oil-phase core-shell nanoprobe.
[0068] Comparative Example 1 2 mmol of ferric acetylacetone, 2.02 mmol of 4-phenylbenzoic acid, 4.50 mmol of oleic acid, and 52.6 mmol of dibenzyl ether were stirred in a 50 mL three-necked flask to obtain a second mixture. The second mixture was placed in a temperature-controlled apparatus and, under magnetic stirring, degassed at room temperature for 1 h to remove oxygen. Subsequently, N2 protective gas was introduced into the second mixture, and the temperature was increased to 290 °C at a rate of 20 °C / min and maintained for 0.5 h. After the reaction was complete, the mixture was cooled to room temperature. Oil-phase magnetic core Fe3O4 nanoparticles were obtained by washing with n-hexane and anhydrous ethanol.
[0069] Comparative Example 2 0.566 mmol of ferric acetylacetone, 0.5 mmol of cobalt acetylacetone, 2.02 mmol of 2-phenylbenzoic acid, 3.80 mmol of oleic acid, and 56.0 mmol of dibenzyl ether were placed in a 50 mL round-bottom flask and mixed thoroughly. The mixture was then placed in a temperature-controlled instrument and degassed for 1 h under magnetic stirring. The temperature was then increased to 290 °C at a rate of 3.3 °C / min and maintained at this temperature for 0.5 h to allow for thermal decomposition. After the reaction was complete, the mixture was cooled to room temperature. The oil-phase nanoshell CoFe₂O₄ nanoparticles were obtained by washing with n-hexane and anhydrous ethanol.
[0070] To further illustrate the beneficial effects of the present invention, a comparative test was conducted between Embodiment 1 of the present invention and Comparative Examples 1-2, see [link to relevant documentation]. Figure 2 The morphology of the oil-phase magnetic core Fe3O4 nanoparticles prepared in Comparative Example 1 was characterized by transmission electron microscopy. It was observed that the synthesized oil-phase magnetic core Fe3O4 nanoparticles possessed a regular cubic structure with a particle size of approximately 17 nm. See also... Figure 3 The morphology of the oil-phase nanoshell CoFe2O4 nanoparticles prepared in Comparative Example 2 was characterized by transmission electron microscopy. The synthesized nanoshell CoFe2O4 nanoparticles exhibited a regular cubic structure with a particle size of approximately 21 nm. See also Figure 4 The morphology of the oil-phase core-shell nanoprobe (SHNP) nanoparticles prepared in Example 1 was characterized by transmission electron microscopy. It was observed that the synthesized oil-phase SHNP nanoparticles possessed a regular cubic structure with a particle size of approximately 23 nm. Compared to the nanoparticles of Comparative Examples 1 and 2, the size of the oil-phase SHNP nanoparticles prepared in Example 1 was increased, suggesting a shell thickness of approximately 3 nm.
[0071] The nanoparticles synthesized in Comparative Examples 1, 2, and 1 were dissolved in 10 mL of tetrahydrofuran solution, mixed thoroughly, and then dissolved in 10 mL of tetrahydrofuran containing 1 g of polymaleic anhydride-1-octadecene. After thorough mixing, the mixture was reacted for 3 h under magnetic stirring, and then the tetrahydrofuran was removed by rotary evaporation at 45 °C. Next, 20 mL of an aqueous solution containing 1 g of dimethylpyridine was added, and the mixture was sonicated for 30 min until all particles were dissolved. The particles were then washed with water and centrifuged four times at 16000 rpm / min for 2 h each time to obtain aqueous nanoparticles. The hydrated particle size of the aqueous nanoparticles prepared using Example 1 and Comparative Examples 1-2 was characterized, see [link to relevant documentation]. Figure 5 The hydrated particle sizes of the three were 21.54, 24.36, and 28.21 nm, respectively, all larger than those obtained by transmission electron microscopy (TEM). This is likely because the surface of the particles after conversion to aqueous phase is coated with a hydrophilic polymer layer formed by polymaleic anhydride-1-octadecene and dimethylpyridine. This coating layer not only has a thickness of approximately 3-5 nm, but also further adsorbs water molecules in the aqueous phase to form a dense dynamic hydration layer accompanied by electrical bilayer expansion, resulting in a significantly larger hydrated particle size than that measured by TEM. However, the increased particle size of the aqueous core-shell nanoprobe (SHNP) also proves the successful synthesis of its particles.
[0072] Fe3O4 and CoFe2O4 were physically mixed at a mass ratio of 1:1 (denoted as S+H). The hysteresis loops of the mixed particles were characterized and compared. (See [link to relevant documentation]). Figure 6 Only the nanoparticles physically mixed with Fe3O4 and CoFe2O4 exhibited a non-smooth hysteresis loop, proving that the particle is a mixture of two phases; the other three groups of particles all had smooth hysteresis loops, and Fe3O4 had the highest magnetic susceptibility and the lowest coercivity, meaning that the particle had a high signal intensity; the smooth hysteresis loop of the core-shell nanoprobe (SHNP) particles also proved that its core Fe3O4 and shell CoFe2O4 were completely coupled into a single-phase particle, further proving the successful synthesis of the particle.
[0073] Subsequently, the above-mentioned aqueous nanoparticles were characterized by MPS and MPI signal intensities, see [reference needed]. Figure 7 and Figure 8 The MPS and MPI signal intensities show a consistent trend: Fe3O4 > SHNP > CoFe2O4. For SHNP nanoparticles, the outer shell covers the magnetic core signal, resulting in a lower magnetic particle sensing signal for the entire particle. It is expected that a higher magnetic particle signal can be generated by responding to the destruction of the outer structure to expose the magnetic core.
[0074] To further illustrate the beneficial effects of the present invention, pH response tests were performed on the oil-phase core-shell nanoprobe (SHNP) nanoparticles prepared in Example 1: Water-converted core-shell nanoprobe (SHNP) nanoparticles were incubated at room temperature with MES buffer solutions at different pH values (4.4, 5.4, 6.4, 7.4) for the same time (12 h), and with MES buffer solutions at the same pH value of 5.4 for different times (2, 4, 6, 12 h) before MPI signals were measured. See [link to relevant documentation] Figure 9 The greater the acidity of the incubation environment, the greater the change in particle signal; see also Figure 10 As the incubation time increased, the particle signal gradually increased; subsequently, the particle morphology after incubation at pH 5.4 for 2 h was observed using TEM images. (See attached image). Figure 11 The particle shell collapsed after incubation under acidic conditions, which is the reason for the enhanced particle signal.
[0075] To further illustrate the application of the core-shell nanoprobe (SHNP) core-shell nanoparticles prepared in Example 1 of the present invention for tumor diagnosis, mouse modeling tests were conducted: A subcutaneous mouse model of breast cancer was constructed. 100 μL of pH 5.4 MES buffer solution was injected into the entire tumor, followed by intratumoral injection of 25 μL of the synthesized aqueous nanoparticles (400 μg / mL). Scans were then performed at 0 h and 6 h using a magnetic particle imaging system (Magnetic Insight, Inc., USA). Results are shown in [link to results]. Figure 12After 6 hours of response, the core-shell nanoprobe (SHNP) exhibited excellent tumor imaging capabilities, with a 1.24-fold increase in signal intensity, indicating that the core-shell nanoprobe (SHNP) has excellent tumor diagnostic capabilities.
[0076] As mentioned above, the application of core-shell nanoprobes in magnetic particle imaging (MPI) can significantly improve the resolution, sensitivity, and clinical applicability of MPI, promoting its clinical translation and facilitating its application in tumor imaging (including but not limited to breast cancer, lung cancer, colorectal cancer, etc.), gastric ulcers, gout, and other fields. It provides technical support for early tumor diagnosis, intraoperative navigation, and efficacy evaluation.
[0077] The above description is merely a preferred embodiment of the present invention and is not intended to limit the technical solution of the present invention in any way. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can be modified and replaced in several simple ways, and these modifications and replacements are all within the scope of protection covered by the claims.
Claims
1. A method for preparing a core-shell nanoprobe, characterized in that, The core-shell nanoprobe comprises a magnetic core and a responsive magnetic shielding nanoshell located outside the magnetic core. The nanoshell collapses under tumor microenvironment conditions. The saturation magnetization of the magnetic core is ≥50 emu / g, and the coercivity is ≤5 Oe. The saturation magnetization of the nanoshell is <50 emu / g, and the coercivity is >5 Oe. The magnetic core is an oil-phase Fe3O4 nanoparticle, and the nanoshell is CoFe2O4. The preparation method includes the following steps: The magnetic nucleus particles, the first iron source, the transition metal source, phenylbenzoic acid, and oleic acid are dissolved in dibenzyl ether to form a first mixture. The first mixture was degassed and then subjected to pyrolysis to obtain a core-shell nanoprobe.
2. The method for preparing core-shell nanoprobes according to claim 1, characterized in that, The molar ratio of the magnetic nucleus particles, the first iron source, the transition metal source, phenylbenzoic acid, oleic acid and dibenzyl ether is (0.11-0.19):(0.11-0.71):(0.11-0.71):(2-3.65):(3.2-9.5):(42-79).
3. The method for preparing the core-shell nanoprobe according to claim 1, characterized in that, The temperature for pyrolysis of the first mixture is 280-320 °C, the reaction time is 0.5-1 h, and the heating rate is 3-8 °C / min; the first iron source is one or more of ferric acetylacetone, ferric oleate, ferrous acetylacetone, ferrous acetate, and ferrous gluconate; the transition metal source is one or two of cobalt acetylacetone and cobalt acetate.
4. The method for preparing core-shell nanoprobes according to claim 1, characterized in that, The magnetic core particles are oil-phase magnetic core Fe3O4 nanoparticles, and the preparation method of the oil-phase magnetic core Fe3O4 nanoparticles is as follows: The second iron source, phenylbenzoic acid, and oleic acid are dissolved in dibenzyl ether to form a second mixture; The second mixture was degassed and then subjected to pyrolysis to obtain oil-phase magnetic core Fe3O4 nanoparticles.
5. The method for preparing the core-shell nanoprobe according to claim 4, characterized in that, The second iron source is one or more of ferric acetylacetone, ferric oleate, ferrous acetylacetone, ferrous acetate, and ferrous gluconate; in the second mixture, the molar ratio of the second iron source, phenylbenzoic acid, oleic acid, and dibenzyl ether is (1.9-2.8):(2-3.65):(3.2-9.5):(42-79); the temperature for pyrolysis of the second mixture is 280-320 ℃, the heating rate is 15-25 ℃ / min, and the reaction time is 0.5-1 h.
6. The application of the core-shell nanoprobe prepared by the preparation method according to any one of claims 1-5 in the preparation of magnetic particle imaging formulations.
